2020
DOI: 10.3390/ijms21082709
|View full text |Cite
|
Sign up to set email alerts
|

Targeting High Mobility Group Box 1 in Subarachnoid Hemorrhage: A Systematic Review

Abstract: Aneurysmal subarachnoid hemorrhage (aSAH) is a complex and potentially deadly disease. Neurosurgical clipping or endovascular coiling can successfully obliterate ruptured aneurysms in almost every case. However, despite successful interventions, the clinical outcomes of aSAH patients are often poor. The reasons for poor outcomes are numerous, including cerebral vasospasm (CVS), post-hemorrhagic hydrocephalus, systemic infections and delayed cerebral ischemia. Although CVS with subsequent cerebral ischemia is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Rupture of an intracranial aneurysm causes blood to pour in subarachnoid space and leads to a transient increase in global intracranial pressure (ICP). This transient elevated ICP may lead to the release of molecules from damaged brain tissue [ 11 , 15 ]. Molecules from extravasated blood and from damaged brain, being the earliest events in the pathophysiology, seem to be the key initiators of the inflammatory cascade, including the expression of adhesion molecules and infiltration of immune cells (specifically macrophages) [ 11 , 13 , 15 ].…”
Section: Initiators and Drivers Of Inflammation After Asahmentioning
confidence: 99%
See 2 more Smart Citations
“…Rupture of an intracranial aneurysm causes blood to pour in subarachnoid space and leads to a transient increase in global intracranial pressure (ICP). This transient elevated ICP may lead to the release of molecules from damaged brain tissue [ 11 , 15 ]. Molecules from extravasated blood and from damaged brain, being the earliest events in the pathophysiology, seem to be the key initiators of the inflammatory cascade, including the expression of adhesion molecules and infiltration of immune cells (specifically macrophages) [ 11 , 13 , 15 ].…”
Section: Initiators and Drivers Of Inflammation After Asahmentioning
confidence: 99%
“…This transient elevated ICP may lead to the release of molecules from damaged brain tissue [ 11 , 15 ]. Molecules from extravasated blood and from damaged brain, being the earliest events in the pathophysiology, seem to be the key initiators of the inflammatory cascade, including the expression of adhesion molecules and infiltration of immune cells (specifically macrophages) [ 11 , 13 , 15 ]. Infiltrated leukocytes and activated resident microglia start the inflammatory cascade, leading to the release of different inflammation-related cytokines [ 16 ].…”
Section: Initiators and Drivers Of Inflammation After Asahmentioning
confidence: 99%
See 1 more Smart Citation
“…The oozing blood and its degradation products also damage various cells in the surrounding area, releasing DAMPs [75]. The over-expression of the mediators (IL-1, IL-6, and TNF-β) and receptors (TLR-2/4, receptors for advanced glycation end-products) activates the destruction and repair process [76]. Sun et al reported data showing that HMGB1 translocations precede other cytokine increase, HMGB1 may be an early upstream promoter of inflammatory response after SAH.…”
Section: Acute Hydrocephalusmentioning
confidence: 99%
“…The toxic effects of the blood and its degradation products further add to the injury of the brain [1,6]. There is a considerable body of evidence suggesting that during this insult, several damage-associated molecular patterns (DAMPs) are liberated from various cellular compartments, which have the capacity to upregulate inflammation after ligation of their cognizant pattern recognition receptors (PRR) [7][8][9][10][11]. Over the past few years, the concept of early brain injury and delayed brain injury has evolved to consider the events triggered immediately after the sentinel bleed up to 72 h and over 3-14 days or more, respectively [1,6,12,13].…”
Section: Introductionmentioning
confidence: 99%